Rapid actions of aldosterone: lymphocytes, vascular smooth muscle and endothelial cells - Christ, Michael; Wehling, Martin (Steroids, 1999)
The genomic theory of steroid action has been the unquestioned dogma for the explanation of steroid effects over the past four decades. Despite early observations on rapid steroid effects being clearly incompatible with this theory, only recently has nongenomic steroid action been recognized more widely and led to a critical reappraisal of unsolved questions about this dogma. Evidence for nongenomic steroid effects come from all fields of steroid research now, and mechanisms of agonist action are studied with regard to membrane receptors and second messengers involved. A prominent example of a receptor/effector—cascade for nongenomic steroid effects has been described for rapid aldosterone effects in various cell types, including lymphocytes, cultured vascular smooth muscle, and endothelial cells involving nonclassical membrane receptors with a high affinity for aldosterone, but not for cortisol, and phosphoinositide turnover. As another important second messenger, [Ca2+]i is consistently increased by aldosterone within 1-2 min. In vascular smooth muscle cells, calcium is released from perinuclear stores, while in endothelial cells a predominant increase of subplasmalemmal calcium is seen. Effects are half maximal at physiological concentrations of free aldosterone (0.1 nmol/L), while cortisol is inactive up to 0.1 μmol/L; the classical mineralocorticoid antagonist canrenone is ineffective in blocking the action of aldosterone. The data show that intracellular signaling for nongenomic aldosterone effects also involves calcium, but pathways of cell activation may vary between different cell types. Future research will have to target the cloning of the first membrane receptor for steroids, and the evaluation of the clinical relevance of these rapid steroid effects.